High-Grade Transformation (Dedifferentiation) of Acinic Cell Carcinoma of the Parotid Gland: Report of an Unusual Variant - Sarah S. Al-Otaibi; Faiza Alotaibi; Yaseer Al Zaher; Nabil Al Zaher; M. A. Dababo (Case Reports in Otolaryngology)
Acinic cell carcinoma with high-grade transformation of the salivary gland is an unusual variant with less than fifty cases being reported in the literature. It is characterized by a low- and high-grade component juxtaposed with one another and tends to take on a more aggressive clinical course than its low-grade counterpart, suggesting a poor clinical outcome. We, hereby, report a case of acinic cell carcinoma in a 48-year-old woman with a 6-month history of a right parotid facial swelling rapidly increasing in size. The tumor was initially resected; however, residual focal tissue subsequently revealed areas typical of low-grade acinic cell carcinoma as well as high-grade transformation/dedifferentiation via histopathology.